Association between systolic blood pressure variability and severity of cerebral amyloid angiopathy in incident intracerebral hemorrhage - Moullaali, Tom J.; Walters, Rachel; Rodrigues, Mark; Samarasekera, Neshika; Bernal, Jose; Wang, Xia; Humphreys, Catherine; Wardlaw, Joanna M.; Farrall, Andrew; Smith, Colin; Anderson, Craig S.; Al-Shahi Salman, Rustam; et al. (Frontiers in Stroke, 2023)
The role of systolic blood pressure (SBP) variability in the pathogenesis of cerebral amyloid angiopathy (CAA) as an underlying cause of intracerebral haemorrhage (ICH) is unknown. We studied SBP variability before ICH according to CAA severity at autopsy.: We collected office (primary care or hospital clinic) BP readings during 10 years before first-ever ICH onset in adults who died and had brain research autopsy in the Lothian IntraCerebral Haemorrhage, Pathology, Imaging and Neurological Outcome (LINCHPIN), prospective, population-based, inception cohort study. A neuropathologist assessed CAA severity using a histopathological rating scale, masked to BP readings. Functional principal component analysis was used to model SBP levels by time before ICH, and logistic regression models assessed associations of SBP variability indices with CAA severity (moderate-severe vs. absent-mild) adjusted for age, gender, and mean SBP. Results: Among 72 adults (median age 81 [interquartile range 76-86], 56% female, median number of SBP readings 11 [3-19]), patients with moderate-severe CAA had similar mean SBP (143 vs. 145 mmHg, P=0.588) but lower SBP variability (SBP standard deviation [SD]14 vs. 17 mmHg, P=0.033) compared with patients with absent-mild CAA, and their SBP trajectories seemed to differ over 10 years before ICH. The odds of moderate-severe CAA were higher with lower maximum SBP (adjusted OR per 10 mmHg lower: 1.53, 95% confidence interval [